2015
DOI: 10.1108/jcre-02-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Asset management determinants of Polish universities

Abstract: Purpose – The purpose of the paper is to offer insights into university asset management (AM) and describe the impact that the various determinants have on the process of university AM. The process of university AM is influenced by a range of determinants. Design/methodology/approach – A literature review and a case study were used to achieve the research objective. The case study involved two data collection techniques – interviews and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…Other research stated that the lack of quality human resources is an obstacle in implementing regional financial and asset management by Raharja et al (2015). Research by Rymarzak and Trojanowski (2015) states that supervision has a positive effect on asset optimization while revealed that A well-integrated computerbased application system can help the government manage their asset by Suprianto (2015).…”
Section: Based On Summary Of Examinationmentioning
confidence: 99%
“…Other research stated that the lack of quality human resources is an obstacle in implementing regional financial and asset management by Raharja et al (2015). Research by Rymarzak and Trojanowski (2015) states that supervision has a positive effect on asset optimization while revealed that A well-integrated computerbased application system can help the government manage their asset by Suprianto (2015).…”
Section: Based On Summary Of Examinationmentioning
confidence: 99%
“…Coalescence of technologies provide a virtuous circle of data, information and knowledge leading to organisational wisdom and commercial exploitation . Of the four technologies, BIM has widely been espoused as the panacea for improved decision making throughout a building's whole life cycle (Rymarzak and Trojanowski, 2015;Mitchell, 2017).…”
Section: Sondergaardmentioning
confidence: 99%
“…Coalescence of technologies provides a virtuous circle of data , information and knowledge leading to organisational wisdom and commercial exploitation (Zhou et al , 2012). Of the four technologies, BIM has widely been espoused as the panacea for improved decision making throughout a building’s whole life cycle (Rymarzak and Trojanowski, 2015; Mitchell, 2017). However, this inherent decision making ability is rarely expanded into other operational areas such as health and safety (H&S) monitoring during a building’s occupancy and use (Wetzel and Thabet, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Jolicoeur and Barrett (2005) referred asset management as the process of maximising the value of property from the processes of acquisition to disposition according to the owner's objective. This was then supported by the Government of Victoria, Australia, which defined asset management as the process of acquisition, disposal of asset and risk management and cost of the entire asset life cycle (Rymarzak & Trojanowski, 2015).…”
Section: Asset Management and Integrity Practicementioning
confidence: 99%